The usefulness of online questionnaire system among students in higher learning institution - Ab. Aziz, Azizi; Ta'a, Azman; Azzali, Fazli; Osman, Baharudin; Atown, Hyder Yahya (2012)
Questionnaires are used in a wide range of settings to gather information about the views and behavior of individuals to inform people about the specific issues. Feedbacks of the questionnaires are used by the researcher to find an accurate result with supporting of statistical analysis functionalities. However, the resulting from the questionnaire is lack supported by the analyzing functionality.In addition, the overall trends and the performance of each question are analyzed by using the offline equations of the statistics analysis.This research focuses on the development of the questionnaire system by focusing on the ‘built-in' statistical analysis functionalities to facilitate as a test bed. The Online Questionnaire System (OQS) is developed in order to reduce loss of papers, time and effort.The general design methodology is represented by using Unified Model Language (UML). 29 students from higher learning institutions has been selected as a respondents to evaluated this system based on the usability and flexibility of the system.Mostly 44.8% persons very agree that the statistical analysis functions in Online Questionnaire website need to be implemented.